The role of brittleness in hydraulic fracture initiation and propagation mechanisms - Feng, Runhua (Curtin University, 2022)
Brittleness index (BI) is a critical parameter characterizing the deformation regime of geo-materials, controlling the fracture development in underground applications. The goal of this study is to understand the multiscale fluid-driven fracture in geomaterials, and investigate the role of BI in hydraulic fracture propagation. The outcome of this research can facilitate not only laboratory or numerical studies, but also the field applications involving hydraulic fracturing.